Sex-Dependent Alcohol Instrumentalization Goals in Non-Addicted Alcohol Consumers versus Patients with Alcohol Use Disorder: Longitudinal Change and Outcome Prediction - Müller, Christian P.; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Alcoholism-Clinical and Experimental Research, 2021)
Background Alcohol can be instrumentalized to achieve goals that without the drug would either not be achievable or would be so only with considerably more workload. While an understanding of the neurobiological mechanisms of alcohol instrumentalization is emerging, little information is available concerning instrumentalization goals in controlled consumers and how these goals change during the development of an alcohol use disorder (AUD).
CRIS-Team WoS Importer:2021-03-12